From the Nobel prize for physiology to the new training and competitive paradigm of competitive swimming - Obradović Aleksandra (Fizička Kultura)
Nitric - monoxide is recognized as a molecule with a very simple structure, considered for a long time as an extremely toxic substance. Yet, due to the possibility of endogenous biosynthesis and the variety of biological actions it possesses, today it is considered as paracrine substance of exceptional pharmacological, physiological and pathophysiological interest. Bearing in mind the numerous negative ecological and health effects that it has on the human environment on a daily basis, extremely large initial efforts have been made for decades to suppress it to a certain extent.. However, the discoveries that, in the eighties of the last century, led to new scientific advances in the fields of chemistry, physiology and medicine, led to a stunning conclusion - that the survival of the most dominant species on Earth mostly depends on its (bio)synthesis. Depending on the concentration, it performs a dual role in the vasculature, since in lower concentrations it has the function of an extremely powerful vasodilator, while in the case of high concentrations it performs the role of cytotoxin and cytostatic, thereby contributing to the body's defense against parasitic infections and tumors. Maintaining its availability in the endothelium is crucial for the normal functioning of the cardiovascular system. The Nobel Prize, which was awarded in 1998. for the discovery of the signaling role of nitric oxide in the human body, opened up a series of specific questions, which primarily relate to the place and role of this molecule in various biochemical processes that constantly occur in the human body under different conditions. Accordingly, the theoretical and empirical issues of the role of nitric oxide in swimming, training, and the general health of swimmers (athletes) in water are the subject of this paper.